Yield performance of some transplant aman rice varieties as influenced by different levels of nitrogen (Journal of the Bangladesh Agricultural University, 2016)
The experiment was carried out during the period of June to November 2013 at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh with a view to examine the yield performance of some transplant aman rice varieties as influenced by different levels of nitrogen. The experiment consisted of four varieties viz. BRRI dhan49, BRRI dhan52, BRRI dhan56, BRRI dhan57 and four levels of N viz. 0, 46, 60 and 75 kg ha-1. The experiment was laid out in a randomized complete block design with three replications. Variety, levels of N and their interactions exerted significant influence on yield contributing characters and yield of transplant aman rice. Among the varieties, BRRI dhan52 produced the tallest plant (117.20 cm), highest number of effective tillers hill-1 (11.28), grains panicle-1 (121.5) and 1000-grain weight (23.65 g) whereas the lowest values of these parameters were produced by BRRI dhan57. Highest grain yield (5.69 t ha-1) was obtained from BRRI dhan52 followed by BRRI dhan49 (5.15 t ha-1) and the lowest one (4.25 t ha-1) was obtained from BRRI dhan57. In case of N, the tallest plant (111.70 cm), highest number of total tillers hill-1 (12.34), grains panicle-1 (133.6), 1000-grain weight (24.55 g) and grain yield (5.64 t ha-1) were obtained from 75 kg N ha-1 and the lowest values were obtained from control. BRRI dhan52 fertilized with 75 kg N ha-1 showed best performance with respect to all the parameters studied. The overall results suggest that BRRI dhan52 should be fertilized with 75 kg N ha-1 for getting higher yield under the agro-climatic condition of BAU.J. Bangladesh Agril. Univ. 12(2): 321-324, December 2014